2019
DOI: 10.1080/10131752.2019.1582150
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards English as a Medium of Instruction in Malawian Universities

Abstract: Malawi's language-in-education policies have been through numerous changes since the colonial period. In 1996 a policy directive was announced which encouraged the use of the mother tongue in the early stages of education, before transitioning to English. However, this policy was never effectively implemented and, in 2014, an English-only policy was announced. This has resulted in renewed debate around which languages are suitable for use as mediums of instruction in the country. This article will discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Study findings from the interviews are aligned with previous studies that highlighted the importance of i) ELLs' attitudes towards EMI courses (Jensen & Thøgersen, 2011;& Miao, 2015;Reilly, 2019;Yeh, 2014), ii) ELLs' opinions of the effectiveness of EMI (Chu et al, 2018;Corrales et al, 2016;Fang & Liu, 2020;Huang, 2015), iii) ELLs' self-evaluation of language ability (Belhiah & Elhami, 2015;Coşgun & Hasırcı, 2017), and iv) challenges that ELLs faced while taking EMI courses (Tsou & Kao, 2017;Walkinshaw et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Study findings from the interviews are aligned with previous studies that highlighted the importance of i) ELLs' attitudes towards EMI courses (Jensen & Thøgersen, 2011;& Miao, 2015;Reilly, 2019;Yeh, 2014), ii) ELLs' opinions of the effectiveness of EMI (Chu et al, 2018;Corrales et al, 2016;Fang & Liu, 2020;Huang, 2015), iii) ELLs' self-evaluation of language ability (Belhiah & Elhami, 2015;Coşgun & Hasırcı, 2017), and iv) challenges that ELLs faced while taking EMI courses (Tsou & Kao, 2017;Walkinshaw et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have documented how EMI can impact ELLs' course attitudes and satisfaction (Jensen & Thøgersen, 2011;Muthanna & Miao, 2015;Reilly, 2019;Yeh, 2014). For instance, Muthanna and Miao (2015) found that ELLs showed positive attitudes towards the EMI courses.…”
Section: Ells' Attitudes Towards Emi Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Malawi, her policy used to encourage the use of mother tongue because it is endangered, controversy came in with the implementation of English as a language to be used in the country's universities. The students and the staff display positive attitudes for multilingual language skills(Reilly, 2019). Meanwhile, Nguyen and Hamid (2018) see bilingualism as a resource in the case of Vietnamese ethnic minority students' attitudes towards informal and formal language policies in different domains such as the church, school, ethnic community as well as towards their individual bilingualism.…”
mentioning
confidence: 99%